Impacts of HER2 immunohistochemical scores on response and outcomes of HER2-positive breast cancers after neoadjuvant therapy. Issue 4 (23rd January 2023) - Chiu, Yun-Ning; Hsu, Chih-Yi; Lien, Pei-Ju; Chao, Ta-Chung; Liu, Chun-Yu; Lin, Yen-Shu; Wang, Yu-Ling; Tsai, Yi-Fang; Tseng, Ling-Ming
Abstract : Background: Neoadjuvant systemic therapy (NST) is conducted in increased number of patients with breast cancer overexpressing human epidermal growth factor receptor 2 (HER2). Whether the intensity of HER2 protein expression determines response to treatment is challenged. This study aims to analyze the impact of HER2 immunohistochemical (IHC) scores on NST response and survival outcome. Methods: We analyzed a total of 197 patients with HER2-positive breast cancer receiving NST and definite surgery from a prospectively collected database. The analyzed endpoints included pathological complete response (pCR), disease-free survival (DFS), and overall survival (OS). More patients with IHC 2+/ in situ hybridization (ISH)-positive tumors presented positive for hormonal receptors, compared with those with IHC 3+ tumors. No clinicopathological features except tumor necrosis were significantly associated with pCR. Results: Both positive hormone receptors and IHC scores stood on the borderline in statistical analysis. IHC 3+ group tends to present a higher pCR rate than IHC 2+/ISH+ groups (52.5% vs. 34.3%). Patients who achieved pCR had better survival outcome than that of non-pCR group. The impact of pCR on survival reached the statistical significance in the IHC 3+ group both in DFS (90.9% vs. 76.5%; p = 0.004) and OS (97.4% vs. 83.2%; p = 0.002). Multivariate analysis demonstrated IHC scores as an independent predictor of survival outcome with the adjustment of tumor staging and pCR. Conclusion: HER2 IHC score is an independent predictor for outcome. IHC 3+ tumors presented a trend of higher pCR rate and better outcome in HER2-positive breast cancer patients who receive NST.